POTENSI BIOMASSA DAN CADANGAN KARBON DI KAWASAN HUTAN MANGROVE DESA KANCI KULON KECAMATAN ASTANAJAPURA KABUPATEN CIREBON - Kartika Sari; Agus Yadi Ismail; Yayan Hendrayana (Faculty of Forestry and Environment, Universitas Kuningan, 2022)
Mangrove forest ecosystems are located in the tidal zone of seawater, such as swamps, lagoons, river estuaries, and beaches in protected tropical and subtropical coastal areas. Mangrove forests are degraded due to human interests. The transfer of functions has an impact on reducing the ability to sequestrate carbon in the atmosphere and the decomposement of stored carbon through the process of decomposition into the atmosphere. This study aims to determine the potential of biomass and carbon stocks in the mangrove forest area of Kanci Kulon Village, Astanajapura District, Cirebon Regency. The method used is purposive sampling, where the location of the plot is adjusted to the accessibility of existing roads, rivers or canals. The Sampling Intensity used is 10%. Data collection was carried out by creating a plot of sample circles with a radius of 14 m for trees and a radius of 4 m for stakes There are 2 types of mangroves found, namely Avicennia marina (White Flames) and Avicennia alba (Black Flames), the dominating population is in the 1-10 cm diameter class with the Avicennia marina type. Biomass in all types of the largest value is in the diameter class of 11-20 cm with a value of 24,234.76 tons/ha, and the smallest biomass is in the diameter class of 31–40 cm with a value of 791.85 tons/ha, while for carbon in all types the highest value is in the diameter class of 11–20 cm with a value of 11,147.99 tons/ha and the smallest carbon is in the diameter class of 31–40 cm with a value of 364.25 tons/ha. The size of the diameter will affect the biomass of the stand, the larger the diameter of the tree, the larger the biomass produced, and vice versa the smaller the biomass produced is influenced by the small diameter. The greater the biomass, the greater the carbon contentEkosistem hutan mangrove terletak di zona pasang surut air laut, seperti rawa, laguna, muara sungai, dan pantai di kawasan pesisir tropis dan subtropis yang dilindungi. Hutan mangrove terdegradasi karena kepentingan manusia. Transfer fungsi berdampak pada pengurangan kemampuan untuk menyerap karbon di atmosfer dan penguraian karbon yang tersimpan melalui proses dekomposisi ke atmosfer. Penelitian ini bertujuan untuk mengetahui potensi stok biomassa dan karbon di kawasan hutan mangrove Desa Kanci Kulon, Kecamatan Astanajapura, Kabupaten Cirebon. Metode yang digunakan adalah purposive sampling, dimana lokasi plot disesuaikan dengan aksesibilitas jalan, sungai atau kanal yang ada. Intensitas pengambilan sampel yang digunakan adalah 10%. Pengumpulan data dilakukan dengan membuat plot lingkaran dengan radius 14 m untuk pohon dan radius 4 m untuk pancang. Terdapat 2 jenis mangrove yang ditemukan, yaitu Avicennia marina (Api-api Putih) dan Avicennia alba (Api-api Hitam), populasi yang mendominasi berada di kelas berdiameter 1-10 cm dengan tipe Avicennia marina. Biomassa pada semua jenis nilai terbesar berada pada kelas diameter 11-20 cm dengan nilai 24.234,76 ton/ha, dan biomassa terkecil berada pada kelas diameter 31–40 cm dengan nilai 791,85 ton/ha, sedangkan untuk karbon pada semua jenis nilai tertinggi berada pada kelas diameter 11-20 cm dengan nilai 11.147,99 ton/ha dan karbon terkecil berada di dalam kelas diameter 31-40 cm dengan nilai 364,25 ton/ha. Ukuran diameter akan mempengaruhi biomassa tegakan, semakin besar diameter pohon, semakin besar biomassa yang dihasilkan, dan sebaliknya semakin kecil biomassa yang dihasilkan dipengaruhi oleh diameter yang kecil. Semakin besar biomassa, semakin besar kandungan